Structural stability in potassium doped single-walled carbon nanotubes, and surface functionalization - Kröckel, Claudia; Ludacka, Ursula; Singh, Rajendra; Kotakoski, Jani; Hauke, Frank; Hirsch, Andreas; Reich, Stephanie; Chacón-Torres, Julio C. (Carbon, 2025)
A systematic investigation of potassium intercalated HiPCO-enriched single walled carbon nanotubes (SWCNT) was conducted, with a focus on the material's structural stability after doping and exposure to ambient conditions for 12 months. Three unprecedented aspects have been revealed: i) Semiconducting nanotubes retain the charge transferred from K as predicted for graphite intercalation compounds. Both species, metallic and semiconducting, exhibit charge stabilization for over a week exposed to air. ii) After exposure to air and harsh chemical reaction conditions, the individualized potassium doped SWCNT showed an intact hexagonal lattice, which demonstrated high structural stability. iii) During exposure to air, functionalization sites appeared on the surface of the n-type doped nanotubes, but there was no significant structural damage observed. We confirm that SWCNT species have a high structural stability in diameters above 0.75 nm explained as an adapting process of the electronic structure from the carbon nanotubes towards a high electron doping followed by a remarkable crystalline defect-free tubular structure. This information is highly relevant for the carbon community revealing for the first time the stability of SWCNT after being highly doped and exposed to air. This work highlights for potential applications of SWCNT in the development of bright photoluminescence nanotubes that strongly depend on their structure, defect content, size, and metallicity.
CRIS-Team Scopus Importer:2025-01-31
Keywords: HiPCO enriched SWCNT; n-type doping; Raman spectroscopy; Surface functionalization; Transmission electron microscopy